EFEKTIFITAS MEDIA INTERAKTIF BERBASIS QUIZ MAKER DALAM PEMBELAJARAN ONLINE DI SDIT MUMTAZUL QUR’AN TAMBAKBOYO TUBAN - Wendri Wiratsiwi; Yulia Prastika (Jurnal Muassis Pendidikan Dasar, 2022)
Media is one component in learning that is very important because the media is an intermediary to convey messages from the communicator to the communicant. The use of media in learning aims so that students can easily understand the material presented by the teacher so that the learning objectives can be achieved. So this study aims to describe the effectiveness of using quiz maker-based interactive media in online learning at SDIT Mumtazul Quran Tambakboyo Tuban. The subjects in this study were fourth grade students of SDIT Mumtazul Quran Tambakboyo Tuban in the 2020/2021 school year, totaling 14 students. This research is an experimental research type using One – Group Pretest Posttest Design as the data analysis technique. The research instrument used is a test sheet. The results showed that the results of the N-gain calculation of 0.387 indicated the medium category and the paired sample T test test obtained 4.522 results with a significance of 0.000, so it can be said that there is a significant difference between the pre-test before using the quiz maker-based interactive media and the post-test after using the quiz maker-based interactive media. Based on the results of this study, it can be concluded that quiz maker-based interactive media is effectively used in online learning